PROFIL CERITA UNTUK MENINGKATKAN KECERDASAN EMOSIONAL: APLIKASI ANCANGAN PSIKOLINGUISTIK - Subyantoro, Subyantoro (Universitas Muhammadiyah Surakarta, 2006)
This article aims to describe story profile which can improve emotional intellegence of cognate growth phase child of concrete operational. This Research subjek consist of: (a) cognate growth phase child of concrete operational and (b) narrator (in this case teacher). The Research was conducted in Semarang Town. The Instruments in this research are: (1) instrument to know story profile enthused by cognate growth phase child of concrete operational, (2) instrument to measure emotional intellegence of cognate growth phase child of concrete operational be- fore and after getting story based on figure function analysis at child story, (3) instrument to know executed narrating profile by narrator (teacher). Telling a story, based on figure function analysis in the reality can give picture and assist activity of telling a story that can develop emotional intellegence. The mentioned seen from tendency the increasing of emotional intellegence of child. Narrating execu- tion shall pay attention psychological aspect of child, including type, way of, theme, figure, path, and story background; existence of interaction braid in course of nar- rating between narrator and hearer; and giving of follow-up having a meaning of to child.Â Key words: children story, narrating, and emotional intellegence.Â